Improving Students Activity and Students Learning Outcomes by Using Combined of Team Games Tournament (TGT) and Guide Note Taking (GNT) - Mila Amalia (Universitas Islam Jember, 2018)
The purpose of the research is to describe the students activities in using mix of team games tournament (TGT) and guide note taking (GNT) learning model. To describe the students learning outcomes in using mix of team games tournament (TGT) and guide note taking (GNT) learning model. The kind of the research is PTK with qualitative and quantitative approach. The subjects of the research are students of class VIII at MTs Darul Mukhlashin. With the data collecting method that used in the research are documentation, observation, interview and test. The data analysis method that used is qualitative and quantitative. The results of the research there is increased activity and student learning outcomes.Keywords: TGT, GNT, students activity, and students learning outcomes